Recent developments in photoelectrochemical water-splitting using WO3/BiVO4 heterojunction photoanode: A review - Kalanoor, Basanth S.; Seo, Hyungtak; Kalanur, Shankara S. (Materials Science for Energy Technologies, 2018)
Pairing tungsten oxide (WO3) and bismuth vanadate (BiVO4) to form heterojunction photoanode is a very promising strategy to attain the enhanced photoelectrochemical (PEC) water splitting efficiency. In fact, the PEC efficiency of WO3/BiVO4 heterojunction photoanode performs significantly better than either of the individual materials due to their well-matched band edge positions, efficient charge separation, and light harvesting abilities. In WO3/BiVO4 heterojunction, BiVO4 serves as an excellent visible-light absorber (∼30% sunlight) and WO3 functions as an active electron conductor. Therefore, the optimization of the ratio and structure of WO3 and BiVO4 becomes very crucial to produce maximum PEC efficiency. In this review, the significant efforts and remarkable milestones achieved using WO3/BiVO4 heterojunction photoanode in PEC water splitting is summarized. The various factors that influence the PEC activity of WO3/BiVO4 heterojunction include the nanostructure morphology, charge carrier's dynamics, layers of WO3 and BiVO4, use of catalysts and doping, etc. With WO3/BiVO4 heterojunction photoanode, outstanding PEC performance equal to the theoretical efficiency values (WO3 and BiVO4) has been achieved. The highest photocurrent value of about 6.72 mA cm−2 (at 1.23 V vs. reversible hydrogen electrode (RHE)) with an incident photon to current efficiency of 90% (at 1.23 V vs. RHE) has been reached. Finally, the future research work direction for designing the high efficiency heterojunction photoanodes using WO3 and BiVO4 is discussed.
Keywords: Band edge position; Bismuth vanadates; Charge-separation; Light-harvesting; Photo-anodes; Photoelectrochemical water splitting; Photoelectrochemical water splitting efficiencies; Photoelectrochemicals; Reversible hydrogen electrodes; Visible light; Bismuth; Efficiency; Heterojunction; Photoanodes; Tungsten